Politik Pencitraan dalam Wacana Gelandangan dan Pengemis: Analisis Jaringan Teks Pasca Pengangkatan Tri Rismaharini sebagai Menteri Sosial RI - Delfirman, Delfirman; Erwinsyah, Rudy G.; As'adhanayadi, Bilal (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2024)
The issue of vagrants and beggars is often used by officials or political figures to gain public attention through news in the mass media. As happened in the news about Tri Rismaharini after being appointed as the Minister of Social Affairs of the Republic of Indonesia. This research uses the Textual Network Analysis (TNA) method on mass media coverage, then relates it to branding politics. Data collection was carried out using web scraping, by taking samples of news coverage on online news portals in the period December 2020 to January 2021. The results show that there are five main clusters in the discourse on vagrants and beggars. "Risma" and "Social" are the nodes with the highest level of centrality in the discourse, which shows high interconnectedness with other nodes. The branding politics carried out can be seen from the use of symbols that become differentiators and the authenticity raised from the central character, by showing her closeness and concern for the fate of vagrants and beggars in the capital city.